2022
DOI: 10.30682/nm2205f
|View full text |Cite
|
Sign up to set email alerts
|

Oasis extension trajectories in Kebili territory, southern Tunisia: drivers of development and actors’ discourse

Abstract: Since the 1970s, the Kebili region southern Tunisia has undergone significant territorial changes due to the expansion of date palm plantations based on illicit boreholes tapping the underlying deep aquifers. These private initiatives, called “extensions”, have developed on collective unfarmed areas, outside historical oases and have raised sustainability concerns. To address the groundwater sustainability, local actors need to build a joint vision of on-going dynamics. The objective of this study is: (i) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
(25 reference statements)
0
6
0
2
Order By: Relevance
“…Mekki et al 94 reported a rise in the illicit use of SPIS in South Tunisia's Kebili region, particularly in the areas disconnected from the ancient oasis, during the period from 2015 and 2020. This increase was marked by the deployment of 2400 SPIS systems (Fig.…”
Section: Energy Irrigation Nexusmentioning
confidence: 99%
“…Mekki et al 94 reported a rise in the illicit use of SPIS in South Tunisia's Kebili region, particularly in the areas disconnected from the ancient oasis, during the period from 2015 and 2020. This increase was marked by the deployment of 2400 SPIS systems (Fig.…”
Section: Energy Irrigation Nexusmentioning
confidence: 99%
“…Water availability and irrigation frequency emerge as key factors in the layout of irrigated areas in Kebili Region. Mekki et al (2022) assess changes in the agricultural landscape in the same Kebili Region. These authors also provide an overview of the socio-economic and environmental drivers of these changes, and analyse local actors' perceptions of these changes.…”
Section: Four Topicsmentioning
confidence: 99%
“…Farmers using irrigated agroecosystems in North Africa have introduced many innovations to get sufficient irrigation water based on both new farming practices and on different forms of agreements between water providers and irrigators (Daoudi et al, 2017). However, these initiatives have not been matched by institutional innovations for the management of water resources at regional level (Mekki et al, 2022). Groundwater depletion patterns have emerged in Kebili and Todgha Regions (Er-rayhany et al, 2022;Mekki et al, 2022).…”
Section: Water Management From Farm To Socioecosystem Levelmentioning
confidence: 99%
See 2 more Smart Citations